Thrombomodulin in patients with mild to moderate bleeding tendency. Issue 6 (10th October 2021) - Mehic, Dino; Tolios, Alexander; Hofer, Stefanie; Ay, Cihan; Haslacher, Helmuth; Downes, Kate; Haimel, Matthias; Pabinger, Ingrid; Gebhart, Johanna
Abstract: Introduction: A massive increase of soluble thrombomodulin (sTM) due to variants in the thrombomodulin gene (THBD) has recently been identified as a novel bleeding disorder. Aim: To investigate sTM levels and underlying genetic variants as a cause for haemostatic impairment and bleeding in a large number of patients with a mild to moderate bleeding disorder (MBD), including patients with bleeding of unknown cause (BUC). Patients and methods: In 507 MBD patients, sTM levels, thrombin generation and plasma clot formation were measured and compared to 90 age‐ and sex‐matched healthy controls. In patients, genetic analysis of the THBD gene was performed. Results: No difference in sTM levels between patients and controls was found overall (median ([IQR] 5.0 [3.8‐6.3] vs. 5.1 [3.7‐6.4] ng/ml, p  = .762), and according to specific diagnoses of MBD or BUC, and high sTM levels (≥95th percentile of healthy controls) were not overrepresented in patients. Soluble TM levels had no impact on bleeding severity or global tests of haemostasis, including thrombin generation or plasma clot formation. In the THBD gene, no known pathogenic or novel disease‐causing variants affecting sTM plasma levels were identified in our patient cohort. Conclusion: TM‐associated coagulopathy appears to be rare, as it was not identified in our large cohort of patients with MBD. Soluble TM did not arise as a risk factor for bleeding or altered haemostasis in these patients.